ANALISIS FATWA DEWAN SYARIAH NASIONAL MAJELIS ULAMA INDONESIA NO: 141/DSN-MUI/VIII/2021TENTANG PEDOMAN PENDIRIAN DAN OPERASIONAL KOPERASI SYARIAH - Desti Rainawati; Husnul Khotimah (Universitas Islam Negeri Mataram, 2024)
Cooperatives according to the Fatwa of the National Sharia Council-Indonesian Ulema Council, NO: 141/DSN-MUI/VIII/2021 concerning guidelines for the establishment and operation of sharia cooperatives, sharia cooperatives are business entities consisting of one person or a cooperative legal entity that bases its activities on cooperative principles as well as as a people's economic movement based on the principle of kinship based on sharia principles. This research will try to examine the background of the Fatwa of the National Sharia Council-Indonesian Ulema Council, No: 141/DSN-MUI/VIII/2021 concerning Guidelines for the Establishment and Operation of Sharia Cooperatives and try to see the ijtihad method used by the MUI using the nash qathi, qawli and manhaji approaches. Analyzing the background of the fatwa here uses the concept of maslahah murlah to determine the benefits of determining the fatwa. Based on the research results, it was found that the background in making the fatwa was to try to provide an answer to the legal certainty of sharia cooperatives in response to the request from the Ministry of Cooperatives and SMEs and to emphasize that existing sharia cooperative businesses are in accordance with the provisions of Islamic law.